Germline but not somatic de novo mutations are common in human congenital diaphragmatic hernia. Issue 7 (23rd March 2018) - Matsunami, Nori; Shanmugam, Hari; Baird, Lisa; Stevens, Jeff; Byrne, Janice L.; Barnhart, Douglas C.; Rau, Carrie; Feldkamp, Marcia L.; Yoder, Bradley A.; Leppert, Mark F.; Yost, H. Joseph; Brunelli, Luca
Abstract : Objectives: Congenital diaphragmatic hernia (CDH) is a developmental defect of the diaphragm that causes high newborn morbidity and mortality. CDH is considered to be a multifactorial disease, with strong evidence implicating genetic factors. Although recent studies suggest the biological role of deleterious germline de novo variants, the effect of gene variants specific to the diaphragm remains unclear, and few single genes have been definitively implicated in human disease. Methods: We performed genome sequencing on 16 individuals with CDH and their unaffected parents, including 10 diaphragmatic samples. Results: We did not detect damaging somatic mutations in diaphragms, but identified germline heterozygous de novo functional mutations of 14 genes in nine patients. Although the majority of these genes are not known to be associated with CDH, one patient with CDH and cardiac anomalies harbored a frameshift mutation in NR2F2 (aka COUP‐TFII ), generating a premature truncation of the protein. This patient also carried a missense variant predicted to be damaging in XIRP2 (aka Myomaxin), a transcriptional target of MEF2A . Both NR2F2 and MEF2A map to chromosome 15q26, where recurring de novo deletions and unbalanced translocations have been observed in CDH. Conclusions: Somatic variants are not common in CDH. To our knowledge, this is the second case of a germline de novo frameshift mutation in NR2F2 in CDH. Since NR2F2 null mice exhibit a diaphragmatic defect, and XIRP2 is implicated in cardiac development, our data suggest the role of these two variants in the etiology of CDH, and possibly cardiac anomalies.